2018
DOI: 10.1007/s00269-018-0962-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of type-B carbonate content on the elasticity of fluorapatite

Abstract: The mechanical behavior of carbonate-bearing fluorapatite (CFAP) (with up to 5.5 wt% CO ) was investigated at high pressure up to 7 GPa. (Framont region, France). Preliminary characterization at ambient conditions was done by single-crystal X-ray diffraction study. The structure refinements, in space group P6 /m, confirm a type-B substitution of the phosphate (PO ) group by the carbonate ion (CO ) . The site occupancies for the C atom are 0.04 for FOW and 0.11 for FRA CFAP, in quite good agreement with the 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…The two sites for carbonate substitution in apatite each control the crystal's perfection and crystallite size, according to different environmental conditions. The B-type carbonate is specific for apatite formation of biominerals under physiological conditions [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…The two sites for carbonate substitution in apatite each control the crystal's perfection and crystallite size, according to different environmental conditions. The B-type carbonate is specific for apatite formation of biominerals under physiological conditions [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Bioapatites display a broad peak at 1430 cm –1 assigned to the ν 3 CO 3 band (Figure S9a). This peak is absent in the Durango apatite which is magmatic-hydrothermal (Figure S9b). Sulfur, which was not measured, typically amounts to less than 2.0 wt % in bioapatite from deep-sea pelagic sediments. ,,, Notwithstanding the exact reasons for the deviation of the chemical sums from 100 wt % total, a plot of the concentrations of the four REY detected by EPMA (Y, La, Ce, Nd) and their concentrations measured by LA-ICP-MS shows excellent agreement between the two analyses (Table S7 and Figure S10, R 2 = 0.996).…”
Section: Discussionmentioning
confidence: 99%
“…Bioapatites display a broad peak at 1430 cm -1 assigned to the ν3 CO3 band (Figure S9a). [90][91][92][93] This peak is absent in the Durango apatite which is magmatichydrothermal 94 (Figure S9b). Sulfur, which was not measured, typically amounts to less than 2.0 wt % in bioapatite from deep-sea pelagic sediments.…”
Section: Geochemical Enrichment In Reymentioning
confidence: 99%
“…An area of interest has centered around the effects of substitution of anions that reside in the halogen site, and how solid solution affects the site location (Murayama et al 1986;Hughes et al 1989Hughes et al , 2014. A number of studies have also been conducted to characterize apatite's structural behavior and phase stability at high pressure (Brunet et al 1999;Comodi et al 2001;Matsukage et al 2004;Konzett and Frost 2009;Konzett et al 2012;Cámara et al 2018). Previous studies have shown that fluorapatite persists to 18.3 GPa at room temperature, but decomposes into an assemblage containing tuite, γ-Ca 3 (PO 4 ) 2 , at ~12 GPa and temperatures above 1000°C (Sugiyama and Tokonami 1987;Matsukage et al 2004).…”
Section: Introductionmentioning
confidence: 99%